Animasi Kitab Suci sebagai Upaya Meningkatkan Kecintaan Anak dan Remaja terhadap Kitab Suci - Bhodo, Yohanes Donbosko; Nuwa, Damianus Dionisius; Kopong, Primiaty Natalia Sabu; Biru, Maria Anjelita; Bida, Maria Magdalena; Lendu, Maria Magdalena; Wuda, Margaretha Apriliani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
One of the concerns raised in the pastoral panorama during the Eighth Pastoral Assembly (Muspas) of the Archdiocese of Ende is the lack of interest among children and teenagers in activities related to the Holy Scriptures. This reality is also keenly felt in the pastoral work of the Quasi-Parish of St. Charles Borromeo in Orakeri. Generally, Catholic children and teenagers lack enthusiasm and quickly become bored with Sekami activities that are too monotonous and lacking in variety. Furthermore, the limited number of competent leaders at the parish level and the lack of knowledge about the Scriptures contribute to the decreasing interest and affection of children and teenagers towards the Holy Scriptures. This service activity is conducted for the target groups of Catholic children and teenagers in the Quasi-Parish of St. Charles Borromeo in Orakeri Ende. The main objective is to enrich knowledge about the Holy Scriptures, hone skills in relation to Scripture literacy, and enhance the love of children and teenagers for the Holy Scriptures. The method used in this activity is a qualitative method that involves participatory action research in the form of lectures and simple yet meaningful practices, involving many participants. Activities include: introducing the Holy Scriptures with the help of cheers, movements, songs, and animated videos; Scripture literacy through training in reading and speaking the Scriptures, composing scripts and dramatizing the Scriptures, as well as various competitions related to the Scriptures. This combination of methods is aimed at minimizing participant boredom while simultaneously encouraging the development of cognitive, affective, and psychomotor aspects among the participants. Consequently, the results achieved are that Catholic children and teenagers have a deeper understanding of the Holy Scriptures, sharpen skills related to Scripture literacy, and grow in their love for the Holy Scriptures.